Design of Intelligent Window Closing System. (June 2020) - Qu, Na; You, Wen
Abstract: In today's society, windows are mainly used in people's home life in manual switching mode, and with the improvement of the quality of life, the perspective of intelligent home is gradually being realized. It has become a topic that people often talk about. This design is based on the stc series single-chip microcomputer as the main control chip. The rain sensor is used to detect whether the rainwater enters the house. Whether the concentration of inhalable particles in the environment is too large and take corresponding measures, the wind speed sensor detects the strength of the wind, and finally the stepper motor is required to complete the function of the window's active opening and closing itself, so that the window has intelligent functions. Circuit components are relatively practical and reliable, so they have the characteristics of simple circuits, economical and applicable, and easy maintenance.